Analisis Sektor Unggulan dan Pola Pergeseran Pada Sektor Pertanian Kabupaten Musi Rawas Utara Provinsi Sumatera Selatan - Berliawan, Febi Rama Putri; Ridwansyah, Muhammad; Bhakti, Adi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
Abstract Research objectives to determine the contribution of the agricultural sector to the economy which is the basis sector in North Musi Rawas Regency, determine the position of the agricultural sector which is the leading sector in North Musi Rawaas Regency, find out the pattern of shifting growth towards the agricultural sector in the economy of North Musi Rawas Regency. Methods that use secondary data. The results of this study show that the analysis of the contribution of the agricultural sector makes a large contribution to the GRDP of North Musi Rawas Regency, namely the plantation sub-sector and the livestock sub-sector. Based on the LQ and DLQ analysis, North Musi Rawas Regency has one leading agricultural sector with more than one LQ and DLQ, namely the plantation sub-sector. Furthermore, the shift in the agricultural sector in North Musi Rawas Regency can be seen using the Shift Share analysis. Where it is known that the agricultural sector of North Musi Rawas Regency, its production growth is included in a developing sector. Changes in the food crops, horticultural, fisheries and agricultural services and hunting subsectors have increased. Based on the shift share of the agricultural sector, it can increase both nationally and in the Province of South Sumatra, where the plantation sub-sector grows. Keyword : Contribution of agriculture sector, leading sector, and shift pattern Abstrak Tujuan Penelitian untuk mengetahui kontribusi sektor pertanian terhadap perekonomian yang menjadi sektor basis di Kabupaten Musi Rawas Utara, mengetahui posisi sektor pertanian yang menjadi sektor unggulan di Kabupaten Musi Rawaas Utara, mengetahui Pola pergeseran pertumbuhan terhadap sektor pertanian pada perekonomian Kabupaten Musi Rawas Utara. Metode yang menggunakan data sekunder. Hasil penelitian ini menunjukan Analisis Kontribusi sektor pertanian memberikan kontribusi yang besar terhadap PDRB Kabupaten Musi Rawas Utara adalah subsektor perkebunan dan subsektor pertenakan. Berdasarkan analisis LQ dan DLQ bahwa Kabupaten Musi Rawas Utara memiliki satu sektor pertanian yang unggulan dengan nilai LQ dan DLQ lebih dari satu, yaitu subsektor perkebunan. Selanjutnya pergeseran sektor pertanian di Kabupaten Musi Rawas Utara dapat dilihat menggunakan analisis Shift Share. Dimana diketahui bahwa sektor pertanian Kabupaten Musi Rawas Utara pertumbuhan produksinya termasuk kedalam sektor yang berkembang. Perubahan subsektor tanaman pangan, hortikultural, perikanan dan jasa pertanian dan pemburuan mengalami peningkatan. Berdasarkan shift share sektor pertanian dapat meningkat baik di nasional maupun di Provinsi Sumatera Selatan yang pertumbuhanya subsektor perkebunan.Kata kunci : Kontribusi sektor pertanian, Sektor unggulan, dan Pola pergeseran.